Functional implications of age differences in motor system connectivity - Langan, Jeanne; Peltier, Scott; Bo, Jin; Fling, Brett W.; Welsh, Robert C.; Seidler, Rachael D. (Frontiers in Systems Neuroscience, 2010)
Older adults show less lateralized task-related brain activity than young adults. One potential mechanism of this increased activation is that age-related degeneration of the corpus callosum (CC) may alter the balance of inhibition between the two hemispheres. To determine whether age differences in interhemispheric connectivity affect functional brain activity in older adults, we used magnetic resonance imaging (MRI) to assess resting functional connectivity and functional activation during a simple motor task. We found that older adults had smaller CC area compared to young adults. Older adults exhibited greater recruitment of ipsilateral primary motor cortex (M1), which was associated with longer reaction times. Additionally, recruitment of ipsilateral M1 in older adults was correlated with reduced resting interhemispheric connectivity and a larger CC. We suggest that reduced interhemispheric connectivity reflects a loss of the ability to inhibit the nondominant hemisphere during motor task performance for older adults, which has a negative impact on performance.